Comparison of light outputs, decay times, and imaging performance of a ZnS(Ag) scintillator for alpha particles, beta particles, and gamma photons. (February 2021) - Yamamoto, Seiichi; Tomita, Hideki
Abstract: ZnS(Ag) is a scintillator mainly used for alpha particle detection because of the high light output for alpha particles. However, the light output and decay times of ZnS(Ag) for beta particles or gamma photons are not obvious. We therefore measured and compared the light outputs and decay times of ZnS(Ag) for beta particles or gamma photons with that for alpha particles. We measured the pulse height distribution and decay times of ZnS(Ag) for Am-241 alpha particles (5.5 MeV), St-Y-90 beta particles (2.28-MeV maximum energy), and Cs-137 gamma photons (0.66 MeV). The relative light output/MeV for the beta particles and gamma photons was ~2%–~5% of that for alpha particles. Decay time for the beta particles and gamma photons was 2.7 ns–2.8 ns, while that for alpha particles was 61 ns. With the different decay times, pulse shape discrimination of the alpha and beta particles was possible for the ZnS(Ag) radiation-imaging detector. We confirmed that ZnS(Ag) is a suitable scintillator for the detection of alpha particles using energy discrimination as well as pulse shape discrimination. Highlights: Relative light output/MeV of ZnS(Ag) for the beta particles and gamma photons was ~1%–~2.5% of that for alpha particles. Decay time of ZnS(Ag) for the beta particles and gamma photons was 2.7 ns −2.8 ns, while that for alpha particles was 62 ns. Pulse shape discrimination of the alpha and beta particles was possible for the developed ZnS(Ag) radiation-imaging detector.